Surgical repair of graft aneurysm following ascending-to-abdominal aortic bypass - Li, Jin-Dong (J Vasc Surg Cases Innov Tech, 2019)
Graft aneurysm after ascending aorta to abdominal aorta bypass is a rare complication of repair of coarctation of the aorta. We present a case of an aneurysm measuring 75 mm in diameter at the midportion of the prosthetic graft in a 33-year-old man. To prevent aneurysm rupture, redo ascending-to-abdominal aortic bypass was performed through an upper ministernotomy and upper midline laparotomy. No postoperative complications occurred. The patient was successfully discharged on postoperative day 6. Although ascending-to-abdominal aortic bypass can achieve long-term patency, the prosthetic graft still has the rare risk of aneurysm formation, as highlighted in this case. Early diagnosis and timely management of this rare complication are essential in preventing aneurysm rupture.